Integration of AI and OR techniques in constraint programming for combinatorial optimization problems 8th international conference, CPAIOR 2011, Berlin, Germany, May 23-27, 2011, proceedings - Achterberg, Tobias; Beck, J. Christopher (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Integration of AI and OR Techniques in Constraint Programming for Combinatorial Optimization Problems, CPAIOR 2011, held in Berlin, Germany, in May 2011. The 13 revised full papers and 7 revised short papers presented together with 3 invited lectures were carefully reviewed and selected from 35 submissions. The papers are focused on both theoretical and practical, application-oriented issues and present current research with a special focus on the integration and hybridization of the approaches of constraint programming, artificial intelligence, and operations research technologies for solving large scale and complex real life combinatorial optimization problems.